Determination Of Adsorption Constant Of Metal Nickel In Electroplating Waste With Continue Adsorption Method Using Activated Water Hyacinth: Penentuan Konstanta Penjerapan Logam Nikel Pada Limbah Elektroplating Dengan Metode Adsorpsi Secara Continue Menggunakan Adsorben Eceng Gondok Teraktivasi - Emi Erawati; Rossi Al Ahmad (Program Studi S1 Teknik Kimia, Fakultas Teknik, Universitas Setia Budi, 2022)
Electroplating wastewater contains dangerous heavy metals, one of which is nickel (Ni). The content of heavy metals in electroplating wastewater must be reduced so as not to harm the environment and endanger human health. One method that can be used is the adsorption method using water hyacinth powder as an adsorbent. The choice of water hyacinth as an adsorbent because it can reduce metal content in the water. Production of activated water hyacinth powder by washing, drying, and activation process with NaOH. This study aims to determine the effect of variations in packing height and wastewater concentration on Thomas's constant and nickel (Ni) adsorption constant in electroplating wastewater by adsorption method using water hyacinth as adsorbent. Electroplating wastewater were operated in the continuous process at velocity of 120 g/min on to adsorbent storage which has been filled with water hyacinth powder with variations in packing height and electroplating waste concentration. The packing variations used in this study were 6, 8, and 10 cm. Variations in the concentration of waste were 20 and 40 g/mL. The waste samples were analyzed using AAS Spectrophotometer Shimadzu AA-6200. The results obtained indicate that the packaging height and the concentration of wastewater affect the decrease in nickel metal content where the higher the packaging, the higher the adsorption constant (q0). Based on the research the highest value of adsorption efficiency and got in the packing height of 10 cm were 25% and 487.134 mg/g in that order. The lowest values of adsorption efficiency and q0 got in the concentration of 40 g/mL were 16% and 185.428 mg/g respectively. Abstrak Limbah elektroplating memiliki kandungan logam berat yang berbahaya, salah satunya yaitu nikel (Ni). Kandungan logam berat dalam air limbah elektroplating harus dikurangi supaya tidak membahayakan lingkungan dan membahayakan kesehatan manusia. Kandungan logam pada limbah elektroplating dapat dihilangkan melalui metode adsorpsi dengan menggunakan serbuk eceng gondok sebagai adsorben. Pemilihan eceng gondok sebagai adsorben karena bisa mengurangi kadar logam pada air. Pembuatan serbuk eceng gondok yang diaktivasi dengan proses pencucian, pengeringan dan aktivasi dengan NaOH. Penelitian ini bertujuan untuk mengetahui pengaruh variasi tinggi packing dan konsentrasi limbah terhadap efisiensi penjerapan dan tetapan penjerapan logam nikel (Ni) pada limbah elektroplating dengan metode adsorpsi menggunakan eceng gondok sebagai adsorben. Limbah elektroplating dialirkan secara kontinyu dengan kecepatan 120 g/menit ke dalam tabung adsorben yang sudah diisi dengan serbuk eceng gondok dengan variasi tinggi packing dan konsentrasi limbah elektroplating. Variasi tinggi packing yang digunakan dalam penelitian ini adalah 6, 8, dan 10 cm. Variasi konsentrasi limbah sebesar 20 dan 40 g/mL. Sampel limbah kemudian diuji dengan Spektrofotometer AAS Shimadzu AA-6200. Berdasarkan penelitian nilai efisiensi penjerapan dan q0 tertinggi didapatkan pada tinggi packing 10 cm sebesar 25% dan 487,134 mg/g. Nilai efisiensi penjerapan dan q0 terendah didapatkan pada konsentrasi limbah 40 g/mL sebesar 16% dan 185,428 mg/g.